The Metacognitive and Neurocognitive Signatures of Test Methods in Academic Listening - Zhai, Jiayu; Aryadoust, Vahid (Frontiers in Psychology, 2022)
This study aims to investigate whether and how test takers’ academic listening test performance is predicted by their metacognitive and neurocognitive process under different test methods conditions. Eighty test takers completed two tests consisting of while-listening performance (WLP) and post-listening performance (PLP) test methods. Their metacognitive awareness was measured by the Metacognitive Awareness Listening Questionnaire (MALQ), and gaze behavior and brain activation were measured by an eye-tracker and functional near-infrared spectroscopy (fNIRS), respectively. The results of automatic linear modeling indicated that WLP and PLP test performances were predicted by different factors. The predictors of WLP test performance included two metacognitive awareness measures (i.e., person knowledge and mental translation) and fixation duration. In contrast, the predictors of the PLP performance comprised two metacognitive awareness measures (i.e., mental translation and directed attention), visit counts, and importantly, three brain activity measures: the dmPFC measure in the answering phase, IFG measure in the listening phase, and IFG measure in the answering phase. Implications of these findings for language assessment are discussed.